IMPLEMENTASI PENDEKATAN PEMBELAJARAN MENDALAM (DEEP LEARNING) DALAM LITERASI MEMBACA - Susilowati, Eni; Ernawati, Fetty; Fairuz Amin Fuadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the implementation of the Deep Learning approach in improving students’ reading literacy at SD Negeri 3 Mojo, Andong District, Boyolali Regency, and to identify the challenges and strategies associated with its implementation. The Deep Learning approach was selected because it emphasizes meaningful, reflective, contextual, and student-centered learning while fostering critical thinking skills in reading literacy instruction. This study employed a descriptive qualitative approach involving fourth- and fifth-grade teachers as the primary participants, with the principal and students serving as supporting informants. Data were collected through observation, semi-structured interviews, and documentation. Data credibility was ensured through source and technique triangulation, while data were analyzed using the interactive model of Miles and Huberman. The findings revealed that the Deep Learning approach was implemented systematically through lesson planning, instructional practices, and assessment activities. The approach integrated the principles of mindful learning, meaningful learning, and joyful learning into reading literacy instruction. Learning activities were conducted through contextual discussions, reflective exercises, visual and digital media utilization, and Higher Order Thinking Skills (HOTS)-based questioning. The implementation contributed positively to students’ reading comprehension, critical thinking skills, self-confidence, and reading motivation. However, several challenges were identified, including differences in students’ literacy abilities, low reading interest among some students, limited instructional time, and varying levels of teacher understanding of the Deep Learning approach. To address these challenges, teachers and the school implemented reading assistance programs, strengthened the school literacy culture, promoted teacher collaboration, and applied contextual learning strategies. These findings indicate that the Deep Learning approach has significant potential to support active, reflective, and meaningful reading literacy learning in elementary schools while fostering competencies required for 21st-century learning.